The analysis of pregnancies terminated before and after the limit of viability: A medicolegal view. (April 2023) - Terece, Cem; Turan, Gokce; Uckan, Hasan Hüseyin; Eser, Ayla; Ozler, Mustafa Rasit; Gunbay, Suheda; Taner, Mehmet Zeki
Abstract: Purpose: In the present study, the purpose was to determine the indications of pregnancy termination procedures that are performed before and after the limit of viability (between 10 and 22 weeks) in a tertiary center and to investigate the characteristics of the cases in which fetocide procedure was offered after the limit of viability (22 weeks and later). It also aimed to discuss the legal deadline for the fetocide procedure and legal aspect of pregnancy termination. Material and method: The present study was conducted as a result of the retrospective examination of 198 cases who underwent pregnancy termination after the 10th week of pregnancy (the legal limit for voluntary termination of pregnancy in our country) in our clinic and met the study criteria. The cases were divided into two main groups as Early Termination (10–22 weeks) and Late Termination (22 weeks and later). The characteristics of these groups (i.e. reason for termination, termination week) and the characteristics of the cases in which fetocide procedure was performed and the cases that were not (i.e. termination week, reasons for termination) were compared. Results: A total of 171 (86%) cases were under 22 weeks and 27 (14%) were 22 weeks or more. In the cases terminated early, the gestational week was found to be highest [20 + 1 (12+3–21 + 1)] in those with preterm premature rupture of membranes, and lowest in those with fetal gastrointestinal abnormalities. No statistically significant differences were detected between the termination reason and the gestational week in the late-terminated group, and also, although the termination week of 5 patients for whom the fetocide procedure was offered [median = 23 + 1 (22+4–26 + 0] was higher than the week of 22 patients for whom the fetocide procedure was not offered [median = 22 + 4 (22+1–25 + 4], the difference was not found to be statistically significant. Conclusion: Since the majority of pregnancy terminations are performed before the viable period, the need for the fetocide procedure in pregnancy terminations is relatively low, and we think that this rate will decrease even more because the rate of early diagnosis of fetal anomalies increases as a result of developments in ultrasonographic imaging. Families who choose the termination of pregnancy search for other countries with appropriate legislation and the loss of time and the indecision of the family might cause the application of pregnancy termination after the viable period because of the limitations in the legal regulations of countries. Highlights: Most of the cases in which pregnancy termination is performed are before the previable period. The option of termination of pregnancy during the nonviable period is most often recommended due to genetic problems. The decision-making processes of families who are offered the option of termination of pregnancy should be supported as much as possible İt seems reasonable to perform fetocide procedure while the fetus is in the intrauterine period for viable pregnancies that are planned to be terminated.